MILITARY-CONNECTED BOARDS AND FINANCIAL DISTRESS RISK: THE MODERATING ROLE OF SUSTAINABILITY REPORT DISCLOSURE - Mardiana, Fitra; Purwaningsih, Endah Supeni (Assets: Jurnal Akuntansi dan Pendidikan, 2024)
ABSTRACTThis study utilizes rent-seeking and legitimacy theories to investigate the impact of military-connected boards and sustainability report disclosure on financial distress risk. This study's main subject is the non-financial public firms indexed by the Global Reporting Initiative (GRI) and listed on the Indonesia Stock Exchange (BEI) between 2017 and 2022. The findings show a strong positive correlation between the likelihood of financial distress and boards with ties to the military. Conversely, a lower risk of financial distress is significantly associated with higher disclosure in sustainability reports. Additionally, sustainability report disclosure mitigates the adverse effects of military-connected boards on financial distress risk. This study enhances existing knowledge by providing empirical evidence on how military connections and sustainability disclosures influence financial distress risk in a developing country context.ABSTRAKStudi ini menggunakan teori rent-seeking dan legitimasi untuk menyelidiki dampak dewan yang memiliki hubungan dengan militer dan pengungkapan laporan keberlanjutan terhadap risiko kesulitan keuangan. Subjek utama penelitian ini adalah perusahaan publik non-keuangan yang terindeks oleh Global Reporting Initiative (GRI) dan terdaftar di Bursa Efek Indonesia (BEI) antara tahun 2017 hingga 2022. Temuan menunjukkan adanya korelasi positif yang kuat antara kemungkinan terjadinya kesulitan keuangan dan dewan direksi terhubung militer. Sebaliknya, risiko kesulitan keuangan yang lebih rendah secara signifikan dikaitkan dengan pengungkapan yang lebih tinggi dalam laporan keberlanjutan. Selain itu, pengungkapan laporan keberlanjutan memitigasi dampak buruk dewan yang memiliki hubungan dengan militer terhadap risiko kesulitan keuangan. Studi ini meningkatkan pengetahuan yang ada dengan memberikan bukti empiris tentang bagaimana hubungan militer dan pengungkapan keberlanjutan mempengaruhi risiko kesulitan keuangan dalam konteks negara berkembang.